The Efficient Side of Progressive Income Taxation - Giacomo Corneo (Center for Economic Studies and ifo Institute (CESifo), 2000)
This paper examines the allocative implications of progressive income taxation when individuals care about their relative income. It shows that tax progressivity might improve efficiency, and the more so in egalitarian economies. Introducing a progressive income tax can yield a Pareto improvement if pre-tax income is evenly distributed. Implementing undistorted choices of working hours requires a progressive tax schedule, and the optimal degree of progressivity decreases with pre-tax income inequality.
Keywords: 330; Progressive income tax; inequality; social status